استخدام اختبار (Kruskal-Wallis) اللامعلمي لدراسة الفروقات بين العوامل المؤثرة على أوزان الأطفال حديثي الولادة - سعيد خليفة ساسي أقبص; هناء يوسف محمد العريفي (Surman Journal of Science and Technology, 2024)
Nonparametric tests are statistical methods or techniques used in the case of data that do not follow the normal distribution and in the case of not specifying the probability distribution of the data. This study aims to identify how to use the nonparametric Kruskal-Waillis test and its applications using SPSS v27 to determine the most important differences between the factors affecting the weight of newborns in the city of Zawiya. The study was conducted on a random sample consisting of (50) cases of recent births, for the purpose of studying the differences between the factors affecting the weights of newborns. The results of the study showed through the application of the Kruskal-Waillis test that there is a significant effect at a significance level of (0.05) for each of (the level of nutrition of the pregnant mother - the mother’s blood pressure rate - the mother’s blood sugar rate) on the weight of newborns. It also became clear through the application of the Eta Squared coefficient ( ) that there is a significant effect of these factors on the change or differences that occurred in the weights of newborns in the city of Zawiya.